DEVELOPMENT OF SONG-BASED AUDIOVISUAL CHEMISTRY MEDIA TO INCREASE INTEREST IN LEARNING THE MAIN GROUP ELEMENTS - Pradhiana Kharisma D; Jamil Suprihatiningrum; Stevani Nurjanah (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Providing a variety of media to support chemistry learning both at school and independently is essential. This research aims to develop chemistry audiovisual song-based media on Main Group Elements. This research uses the research and development (R&D) method with the 4-D model (define, design, develop, and disseminate). Audiovisual song-based media were validated by content and media experts, assessed by three high school chemistry teachers, and responded to by ten XII-grade high school students. The final product of this development is an audiovisual-based song education media equipped with various features: 1) containing images, animation, and sound, 2) utilizing applications: BandLab, Ibis Paint x, Flipaclip, and Capcut, 3) using the 2013 Curriculum, 4) presenting two musical arrangements for four song titles in one video (noble gases, alkali metals, halogens, and alkaline earth metals) which are then completed with a quiz, and 5) each song presents the sub-material of abundance, physical and chemical properties, as well as the benefits of elements, 6) using appropriate language styles and supporting sentences in the video, and 7) practical. After being declared valid by content and media experts, the song was assessed for quality by three chemistry teachers with an idealized percentage of 93.33% or an outstanding category. The product was then responded to positively by students with an ideal percentage of 98% or a particular category in all aspects.